Anterior Cruciate Ligament Reconstruction Using Allograft in Adults Older Than the Age of 40 Years Shows Similar Patient-Reported Outcomes Between Male and Female Patients - Sean Hazzard, P.A., M.B.A; Blake Bacevich, B.S; Nicholas Perry, M.D; Varun Nukala, B.S; Peter Asnis, M.D (Elsevier, 2024)
Purpose: To evaluate patient-reported outcomes in patients undergoing anterior cruciate ligament (ACL) reconstruction using allograft in patients 40 years of age or older divided by sex. Methods: Patients age 40 years of age or older who underwent ACL reconstruction by the same surgeon using allograft via anteromedial portal technique were retrospectively identified. Patient-reported outcomes (International Knee Documentation Committee [IKDC], Knee Injury and Osteoarthritis Outcome Score, Tegner, Lysholm, Marx, and Single Assessment Numeric Evaluation) were evaluated and recorded, and outcomes were analyzed by sex. Results: In total, 159 patients undergoing primary ACL reconstruction were reviewed. Two-year outcomes were obtained. All patients noted improvement in patient-reported outcome measures. Male patients had overall greater postoperative patient-reported outcomes measures at all time points for IKDC, Tegner, Lysholm, Marx, and Single Assessment Numeric Evaluation scores; however, the only significant time points were IKDC 6 months (P = .016), 1 year (P = .012) and Marx 1 year (P = .007) and 2 year (P = .016). Knee Injury and Osteoarthritis Outcome Score scores similarly showed greater postoperative scores at all time points and statistical significance at 3 months (P = .002), 6 months (P = .033), and 1 year (P = .031). Conclusions: ACL reconstruction in individuals older than the age of 40 years using allograft results in good outcomes compared with preoperative status. Patient-reported outcomes were similar between male and female patients regarding most patient-reported outcome measures. Level of Evidence: Level III, retrospective cohort study.